Pemasangan Pambangkit Listrik Tenaga Surya Tipe Off Grid Kapasitas 120 X 2 WP pada Rumah di Daerah Terpencil - Seda, Fransiskus; Rochani, Rochani; A., Sulaiman (Green Publisher Indonesia, 2025)
Solar panels are a rapidly developing solar power generation technology that serves as a renewable energy solution, particularly in remote areas that are difficult to reach by conventional electricity grids. The main challenges in implementing this technology include low public awareness, high installation costs, and the influence of environmental conditions on its performance. This study aims to analyze the effectiveness and efficiency of off-grid solar panels in generating electricity and to evaluate the environmental factors affecting their performance. The novelty of this research lies in its analytical approach, which considers not only sunlight intensity and solar panel types but also the geographical and socio-economic aspects of the local community. The research method used is an experimental approach by conducting direct testing of a 120 x 2 WP off-grid Solar Power Plant (PLTS) system installed in a household in a remote area. Data was obtained through observation, technical measurements, and documentation. The results showed that the highest voltage produced by the solar panel was 12.5 volts under clear weather conditions, whereas it decreased to 12.1 volts under cloudy conditions. In maximum load testing, the generated electrical power remained sufficient to supply household needs despite a voltage drop. In conclusion, the 120 x 2 WP off-grid PLTS system can serve as an effective energy solution in remote areas, although optimal load management is necessary to maintain energy efficiency.